Pengaruh Perubahan Arus Kas dan Profitabilitas Terhadap Return Saham Pada PT Mayora Indah Tbk - Shinta Anggria Nur; M. Rimawan (Bahtera Inovasi, 2021)
The increase and decrease in cash flow each year shows that the performance of a company is not stable. This is accompanied by the industry average return on investment ratio below 30%, which means that the return on investment is not good. This is because the profit bars obtained decreased drastically in 2014. This study aims to analyze the effect of changes in cash flow and profitability on stock returns at PT Mayora Indah Tbk either partially or simultaneously. This study uses an associative approach. The population of this research is the financial statement data of PT Mayora Indah Tbk for 43 years from 1977 - 2020. The sample of this research is for 12 years from 2009 - 2020. The sampling technique in this study used purposive sampling. The type of data is quantitative research with secondary data sources. The data analysis technique uses the classical assumption test, multiple linear regression analysis, multiple correlation, the coefficient of determination, the T test and the F test using the Statistical Product and Service Solution (SPSS) version 16 program. In this study, operating cash flow, investment cash flow, funding cash flow and return on investment have an effect on stock returns with the magnitude of the effect of 67.1% and the remaining 32.9% is influenced by other factors. Partially, only the investment cash flow variable has a significant effect on stock returns, while the operating cash flow, funding cash flow and return on investment variables have no effect on stock returns. Simultaneously, there is no significant influence on the independent variable operating cash flow, investment cash flow, funding cash flow and return on investment on the dependent variable of stock returns.